New records of myxomycetes for the state of Veracruz from Cofre de Perote National Park - Salazar Hernández, Berlia Beneric (2021)
Most of the species of myxomycetes from Mexico are well documented, but their patchy geographical and temporal distribution responds to the individual efforts carried out in different areas of the territory over time. As such, even for well-studied areas, new projects can substantially increase biodiversity-based information. The present study constitutes an update of the myxomycete catalog of the state of Veracruz, carried out from an intensive study in a section of Abies religiosa at the Cofre de Perote National Park. The methodology consisted in field collections, complemented with a laboratory isolation process using diverse substrates from different locations. The study was carried out in two years (2018-2019) and in two seasons (dry and rainy). A total of 30 taxa were identified, out of which, 21 species were not previously known for the state of Veracruz, increasing the number of myxomycetes known in such state to 168 species, making it one of the most diverse states in Mexico, with approximately 45% of the known species in the country.